Acculturative stress, everyday racism, and mental health among a community sample of South Asians in Texas - Siddiqui, Shan Mohammed (Frontiers in Public Health, 2022)
South Asian Americans are part of the fastest growing racial/ethnic group in the United States and make up a substantial portion of the U.S. immigrant population. Research on this group has often focused on acculturation, the adoption of different values and behaviors in a new sociocultural environment. While there is evidence to suggest that acculturation (and the stress associated with this process) has a negative effect on the health and well-being of Asian Americans, more recent research has emphasized the need to examine the role of broader social forces—including everyday racism—in impacting mental health. Drawing on the stress process model, this study uses an original survey instrument to investigate the relationships between acculturative stress, anti-Asian racism, and mental health among a community sample of 200 South Asians in Texas. Results from hierarchical multiple regression models indicate that both acculturative stress and everyday racism are strongly linked to higher levels of anxiety-related symptoms and more frequent depressive symptoms. Everyday racism, however, explained variance in these outcomes, well beyond the effect of acculturative stress and other sociodemographic factors. These results underscore the potential benefit and importance of including questions about racism in community health surveys that aim to study health disparities among Asian Americans and highlight the persistence of social issues that U.S. South Asians face.